Стиль жизни молодого россиянина, представленный в тематических материалах учебника „Новые встречи - Smędzik, Lucyna (Studia Rossica Posnaniensia, 2015)
The coursebook titled Новые встречи presents a new generation of Russians (i.e. their everyday life: careers, choices, hobbies, etc.). The lifestyles it describes reveal a modern portrait of young Russians, who are European citizens.